Implementing a national approach to universal child and family health services in Australia: professionals' views of the challenges and opportunities. (1st December 2014) - Schmied, Virginia; Homer, Caroline; Fowler, Cathrine; Psaila, Kim; Barclay, Lesley; Wilson, Ian; Kemp, Lynn; Fasher, Michael; Kruske, Sue
Abstract Australia has a well‐accepted system of universal child and family health (CFH) services. However, government reports and research indicate that these services vary across states and territories, and many children and families do not receive these services. The aim of this paper was to explore professionals' perceptions of the challenges and opportunities in implementing a national approach to universal CFH services across Australia. Qualitative data were collected between July 2010 and April 2011 in the first phase of a three‐phase study designed to investigate the feasibility of implementing a national approach to CFH services in Australia. In total, 161 professionals participated in phase 1 consultations conducted either as discussion groups, teleconferences or through email conversation. Participants came from all Australian states and territories and included 60 CFH nurses, 45 midwives, 15 general practitioners (GPs), 12 practice nurses, 14 allied health professionals, 7 early childhood education specialists, 6 staff from non‐government organisations and 2 Australian government policy advisors. Data were analysed thematically. Participants supported the concept of a universal CFH service, but identified implementation barriers. Key challenges included the absence of a minimum data set and lack of aggregated national data to assist planning and determine outcomes; an inconsistent approach to transfer of information about mothers and newborns from maternity services to CFH nursing services or GPs; poor communication across disciplines and services; issues of access and equity of service delivery; workforce limitations and tensions around role boundaries. Directions for change were identified, including improved electronic data collection and communication systems, reporting of service delivery and outcomes between states and territories, professional collaboration, service co‐location and interprofessional learning and development.